KAJIAN TEOLOGIS TENTANG PENGINJILAN DALAM METAVERSE SERTA APLIKASINYA DI DUNIA VIRTUAL - Owen Susanto (The Way: Jurnal Teologi dan Kependidikan, 2023)
Mission and evangelism is a command given by the Lord Jesus. He sent His disciples to make disciples of all nations, baptizing them in the name of the Father, Son, and Holy Spirit, and teaching them to do everything the Lord Jesus had taught them. Mission and Evangelism need to be done by every believer in this modern age. Since Mark Zuckerberg announced about the metaverse, many people have planned to join and take advantage of the opportunity to do business, and seek profit for their personal life. The church should be able to see the metaverse as an opportunity for mission and evangelism, not reject it. The purpose of this study is to explain why the metaverse is an ideal platform for doing missions and evangelism, along with ways to do mission and evangelism in the metaverse. The method used is descriptive qualitative with content analysis techniques. This research is library research. The results of this study indicate that the metaverse can bring a large number of souls to God by creating an attractive virtual environment and according to the times described in the Bible and every believer can carry out missions and evangelism with the principles of experts. The conclusion of this study is that the metaverse can be used by every believer to carry out missions and evangelism, therefore, the church should not be anti-technology, but the church must use the technology, for the glory of God.